Triggers of treatment interruption and resumption among individuals with type 2 diabetes: a narrative cross-sectional qualitative study - Tomoo Hidaka; Rieko Suzuki; Katsue Hashimoto; Mariko Inoue; Shota Endo; Takeyasu Kakamu; Mariko Gunji; Koichi Abe; Tetsuhito Fukushima (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Treatment interruption and resumption are common among people with type 2 diabetes mellitus (T2D), but the triggers of resumption, according to the reasons for interruption, remain underexplored. This study examined patterns of treatment interruption and resumption. Methods Narratives from 13 T2D patients with a history of treatment interruption were analysed through semi-structured interviews. Results Four patterns were identified: 1) “Economic rationality”, where financial barriers caused interruptions, but resumption was facilitated by low-cost check-ups and updated patient mindsets to manage medical expenses within the constraints of a limited household budget; 2) “Proactive information seeking”, where doubts about treatment effectiveness led to interruptions, followed by resumption through active health risk reassessment by the patient’s self-directed efforts; 3) “Health professional-patient relationship”, where conflicts with healthcare providers prompted interruptions, but trustful encounters encouraged resumption; and 4) “Sustained partnerships with community health professionals”, where personal challenges caused interruptions, but non-coercive partnerships with community health professionals fostered resumption through strengthened patient commitment. Conclusion This study highlights the need for tailored medical support and local policy development for T2D patients, emphasizing subjective interpretations of their experiences on treatment interruption and resumption. Recognizing these patterns can guide resource allocation and the design of community-based diabetes care interventions.